Influence of MDM2 SNP309 and SNP285 status on the risk of cancer in the breast, prostate, lung and colon. Issue 1 (10th December 2014) - Gansmo, Liv B.; Knappskog, Stian; Romundstad, Pål; Hveem, Kristian; Vatten, Lars; Lønning, Per E.
Abstract : MDM2 is a key regulator of the p53 tumor suppressor protein and is overexpressed in many human cancers. Two single nucleotide polymorphisms (SNPs) located in the MDM2 intronic promoter (P2) have been found to exert biological function. The G‐allele of SNP309T>G; rs2279744 increases MDM2 transcription and has been linked to increased cancer risk. In contrast, the less frequent SNP285G>C; rs117039649, which is in complete linkage disequilibrium with SNP309 (generating a SNP285C/309G variant haplotype), has been related to reduced MDM2 transcription and to reduced risk of breast, endometrial and ovarian cancer. In this large population‐based case–control study, we genotyped SNP309 and SNP285 in 10, 830 individuals, including cases with cancer of the breast ( n =1, 717), colon ( n =1, 532), lung ( n =1, 331) and prostate ( n =2, 501), as well as 3, 749 non‐cancer controls. We found a slightly reduced risk for lung cancer among individuals harboring the SNP309TG/GG genotypes compared to the SNP309TT genotype (OR= 0.86; CI = 0.67–0.98), but this association was restricted to women (OR = 0.77; CI = 0.63–0.95) and was not present among men (OR = 0.91; CI = 0.77–1.08). Consistent with previous findings, we found a reduced risk for breast cancer among individuals carrying the SNP285GC/309GG genotype versus the SNP285GG/309GG genotype (OR = 0.55; CI = 0.33–0.93). In conclusion, our data support the hypothesis that the effects of both SNP285 and SNP309 status are tissue dependent. Abstract : What's new? The protein MDM2 grabs on to the tumor suppressor p53, stopping its transcription activity. In this study, the authors investigated two MDM2 polymorphisms. The first, SNP309G, has been linked to increased cancer risk; the more recently identified SNP285C may modulate the effects SNP309G. After screening 7, 000 cases and half as many controls, the authors found a tissue‐specific effect. They report that SNP285C accompanies reduced breast cancer risk among those carrying two SNP309G alleles. No association of SNP309 allele with colon, breast, or prostate cancer risk could be detected, but they noted an association of SNP309G with reduced lung cancer risk.